2016
DOI: 10.5435/jaaos-d-14-00289
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Displaced Greater Tuberosity Fractures of the Humerus

Abstract: Greater tuberosity fractures of the humerus can be successfully treated nonsurgically in most patients. However, as little as 3 to 5 mm of superior greater tuberosity displacement may adversely affect rotator cuff biomechanics and lead to subacromial impingement in patients who are active. In these cases, surgical treatment is recommended. Multiple surgical techniques include open and arthroscopic options tailored to fracture morphology, and strategies for repair include the use of suture anchors, transosseous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 45 publications
1
61
0
3
Order By: Relevance
“…With appropriate clinical examination and suspicion, the advanced practice provider should obtained advanced imaging in the form of magnetic resonance imaging or computed tomography ( Fahmy et al, 2011 ;Gumina et al, 2009 ). Attention should be given to any amount of displacement, understanding that a moderately displaced fracture (defi ned as ≥ 5 mm of displacement) is better treated surgically ( Platzer et al, 2008 ;Rouleau et al, 2016 ). As highlighted here, those patients with a nondisplaced or minimally displaced fracture can be treated conservatively ( Mattyasovszky et al, 2011 ;Rath et al, 2013 ).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…With appropriate clinical examination and suspicion, the advanced practice provider should obtained advanced imaging in the form of magnetic resonance imaging or computed tomography ( Fahmy et al, 2011 ;Gumina et al, 2009 ). Attention should be given to any amount of displacement, understanding that a moderately displaced fracture (defi ned as ≥ 5 mm of displacement) is better treated surgically ( Platzer et al, 2008 ;Rouleau et al, 2016 ). As highlighted here, those patients with a nondisplaced or minimally displaced fracture can be treated conservatively ( Mattyasovszky et al, 2011 ;Rath et al, 2013 ).…”
Section: Discussionmentioning
confidence: 96%
“…Although plain radiographs are usually adequate for identifying this pathology, there is potential for a nondisplaced fracture to be missed ( Gumina et al, 2009 ;Mattyasovszky et al, 2011 ;Rouleau et al, 2016 ). With appropriate clinical examination and suspicion, the advanced practice provider should obtained advanced imaging in the form of magnetic resonance imaging or computed tomography ( Fahmy et al, 2011 ;Gumina et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Park TS recommended that GT fractures with a displacement greater than 5 mm should be treated operatively [16]. On the other hand, Rath E had shown that conservative treatment with a displacement of less than 3 mm could achieve clinical results [17][18]. In our study, isolated GT fracture, J.Mutch type, was employed to be our diagnosis.…”
Section: Complicationsmentioning
confidence: 90%